THE DIFFERENCES OF STUDENTS’ TECHNIQUES AND METHODS IN TRANSLATING POEM “ WHITE EYES” BY MARRY OLIVER - ATI SRIMULYATI (Journal of English Education Program (JEEP), 2016)
This study investigated the differences of students’ methods and techniques in translating poem “White Eyes” by Marry Oliver. This study used case study with qualitative data. Qualitative data were obtained from a translation test and questionnaire that consisted of the poem “White Eyes” by Marry Oliver and the questions about that translation. Translation test and questionnaire were designed to analyze the differences of students’ methods and techniques in translation and then what problem the translation do the translator face in translating poem “White Eyes” by Marry Oliver from English into Indonesian. The analysis was done through the following phases: (1) students’ translation of poem was identified, (2) analyzed and compared the methods and techniques they used and (3) classified the methods and techniques. The population of this study was the fourth grade students of English Education Program Faculty of Teacher Training and Education Sciences at Galuh University in Ciamis who took Translation class at 8th term. The writer selected 5 students as the samples of this study. The writer used the purposive sampling techniques to select the sample. The result of this study shows that almost students used more than one technique, there are literal translation technique, adaptation, transposition, modulation, reduction, established equivalent, and the writer concludes that almost students used adaptation method  in translation that poem. Based on the result of this study, the writer concludes that there are some differences of students methods and techniques in translation, but the differences are not significant.